Source localization based on time delay estimation in complex environment - Da-wei ZHANG; Chang-chun BAO; Bing-yin XIA (Tongxin xuebao, 2014)
In order to improve the performance of source localization in noisy and reverberant environments,a novel time delay estimation (TDE) method was proposed.This method is called acoustical transfer function ratio based on statistical model (ATFR-SM).In the proposed algorithm,the noise reduction method based on the statistical model was adopted to reduce the effect of noise on acoustical transfer Function (ATF).In the ATF method,the power spectral density (PSD) was smoothed and whitened to reduce the effect of reverberations.voice activity detection (VAD) was used to distinguish the speech period from the noise period,and the TDE was performed in the speech period to improve the estimation accuracy.Moreover,the proposed TDE method and the linear closed-form method for source localization were combined to constitute a source localization system.The results of performance evaluation show that,in both the noisy and reverberant conditions,the lower percentage of abnormal points (PAP) and lower root mean square error (RMSE) can be achieved by the proposed TDE method than those of the reference methods.Meanwhile,the source localization has higher accuracy than the reference methods.